Purtscher-like Retinopathy in Critically Ill Patients (Non-Traumatic Etiologies): A Systematic Review and Meta-analysis of Incidence, Associated Conditions, and Visual Outcomes - Ramzi Amin; Dina Fatwa (HM Publisher, 2024)
Introduction: Purtscher-like retinopathy (PLR) is an occlusive microvasculopathy presenting with funduscopic findings similar to Purtscher's retinopathy but occurring in the absence of direct head or chest trauma. Its association with various systemic conditions, particularly those requiring intensive care unit (ICU) admission, is recognized, but comprehensive data on its incidence, spectrum of associated non-traumatic critical illnesses, and visual prognosis in this specific population remain sparse. This study aimed to systematically review the literature and perform a meta-analysis to estimate the incidence of PLR among critically ill patients with non-traumatic conditions, identify commonly associated systemic diseases, and quantify visual outcomes. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. PubMed, Embase, Scopus, and Web of Science databases were searched from January 1st, 2013, to December 31st, 2023, for studies reporting PLR in critically ill adult patients admitted for non-traumatic reasons. Studies included cohort studies, case-control studies, and sufficiently large case series (n≥5 with ICU context) reporting incidence or detailed clinical data. Two reviewers independently screened studies, extracted data, and assessed the risk of bias using the Newcastle-Ottawa Scale (NOS). Pooled incidence of PLR, associated conditions, and final visual acuity (logMAR) were synthesized. A random-effects model was used for meta-analysis due to anticipated heterogeneity. Results: 6 studies met the full eligibility criteria for quantitative synthesis, encompassing 960 critically ill patients from various ICU settings. The included studies were predominantly retrospective cohorts with moderate overall quality (median NOS score 7, range 6-8). The pooled estimated incidence of PLR in the evaluated non-traumatic critically ill populations was 3.4% (95% Confidence Interval [CI]: 2.1% - 5.5%), exhibiting substantial heterogeneity (I² = 80%, p < 0.001). The most frequently reported associated conditions were severe acute pancreatitis (reported in 4/6 studies) and sepsis/septic shock (4/6 studies). Other identified associations included acute kidney injury requiring renal replacement therapy, HELLP syndrome in post-partum patients admitted to ICU, and systemic lupus erythematosus/antiphospholipid syndrome flares requiring intensive care. Visual outcomes were generally poor; the pooled mean final best-corrected visual acuity (BCVA) was 0.85 logMAR (approx. Snellen 20/140; 95% CI: 0.65 - 1.05 logMAR), again with significant heterogeneity (I² = 75%). Approximately 45% of affected eyes had a final BCVA of less than 20/200. Conclusion: Purtscher-like retinopathy represented a notable, albeit relatively uncommon, complication among heterogeneous populations of critically ill patients admitted for non-traumatic conditions. It was most frequently associated with severe systemic inflammatory states such as acute pancreatitis and sepsis. Increased awareness and ophthalmoscopic screening in high-risk ICU patients may be warranted. The observed heterogeneity highlights the need for larger prospective studies with standardized diagnostic and reporting criteria.